Uyo Farmers’ Knowledge, Attitude and Perception (KAP) of Broadcast Media Reports on Soil Contamination - Udoudom, Uduak; Ntegwung, Esther; George, Kufre; Igiri, Anthony (Lembaga Yasin AlSys, 2023)
This study was conducted to investigate the Knowledge, Attitude, and Perception (KAP) of farmers in Uyo regarding broadcast media reports on soil contamination. A survey sample of 384 respondents took part in the study. The research assessed the level of awareness among farmers concerning soil contamination as conveyed through broadcast media, as well as their attitudes towards such information and overall perceptions of the issue. Findings showed that Uyo farmers were familiar with the concept of soil contamination. This suggests that the majority of them have been exposed to information about soil contamination through mass media sources. Broadcast media reports on soil contamination provide accurate and reliable information to farmers. Uyo farmers rated broadcast media source of information about soil contamination and agricultural practices as trustworthy. The study recommended that broadcast media reports should be presented in the local language(s) spoken by Uyo farmers and should be tailored to their cultural context. This approach enhances comprehension and receptiveness, fostering a deeper understanding of soil contamination issues and solutions.